Classical and modern principles and resources: their combination in the management of Le Fort fractures - Denia Morales Navarro (Editorial Ciencias Médicas, 2022)
Introduction: Traumatic maxillofacial lesions are an important global health problem, as well as a public health burden. Objective: Reflect on the need to combine classical and modern principles and resources in the management of Le Fort fractures in the Cuban context. Main remarks: Treatment of facial fractures has evolved considerably through the years. Before the appearance of miniplates, stainless steel wire was used for osteosynthesis in maxillofacial surgery. Titanium osteosynthesis systems are currently the systems of choice in maxillofacial surgery. Despite their undeniable advantages, developing countries occasionally do not have all the equipment required for their use. General considerations: Management of maxillofacial trauma is aimed at recovering the original form and function of the affected area. Without disregarding the theoretical principles of the management of Le Fort fractures, Cuban professionals should search for solutions in keeping with the resources available. The combination of classical techniques and modern resources, such as wired craniofacial suspensions, bar arches and maxillomandibular fixation screws, may be a reliable therapeutic alternative.